Odnos študentov zdravstvene nege do e-izobraževanja - Hvalič Touzery, Simona (Obzornik zdravstvene nege, 2015)
Introduction: Over the past decades, e-learning has become an important part of tertiary education, yet it is not always successfully implemented. The success of implementing e-learning in study programmes is influenced by the readiness to embrace this type of learning and by the students' attitudes towards it. The purpose of this research was to identify the nursing students' attitudes to e-learning. Methods: Quantitative research was conducted in March 2014 on a convenience sample of students from the Faculty of Health Care Jesenice (n = 92). Cronbach's alpha was 0.966. The online survey was used as a research instrument. The data gathered were processed with the statistical package SPSS 20.0. The frequency analysis, t-test for independent samples, one-way analysis of variance, correlation, regression and factor analysis were applied. Results: Benefits of e-learning were most highly rated by the students that participated in the e-classroom in three courses (p = 0.000). There are statistically significant differences (p < 0.05) in the students' attitudes based on their level of computer skills. A positive and statistically significant correlation between the students' attitude towards e-learning and the advantages of e-learning (0.211 < % < 0.834, p = 0.000) were established. The following factors can explain 64.72 % of the variability of the common factors of the students' attitude towards e-learning: use of e-classroom, satisfaction with the group work and learning style. Discussion and conclusion: The respondents were not prone to e-learning, yet several factors that positively influence their attitude to e-learning were identified. It would be necessary to extend the survey on a randomly selected representative sample and to use mixed methods research.
Keywords: attitudes; education; educations; e-learning; e-učenje; izobraževanje; naklonjenost; nursing care; student; students; študenti; zdravstvena nega